COMMON FIXED POINT FOR SELF AND NONSELF-MAPS THROUGH AN IMPLICIT RELATION - Surekha, D.; Phaneendra, T. (Italian Journal of Pure and Applied Mathematics, 2014)
Common fixed point theorems for three self and nonself-maps have been proved through the notions of property E.A., orbital completeness and weak compatibility under an implicit relation. The results of Singh and Mishra (1997), Singh and Asish Kumar (2006), Khan and Dolmo (2007) and Imdad and Ali (2008) are then particular cases.